Ernie Allen - SJSU Special Collections & Archives::::::::: (2022)
Ernie Allen attended San Jose State College from 1940-1941. Allen was born in Oakland on November 1, 1918. He was a member of the basketball teams at Oakland Technical High School, Marin Junior College, and San Jose State. Allen was active in civil rights causes, and was the plaintiff in the 1953 lawsuit that ended racial segregation in the Oakland Fire Department. For 43 years, he ran Supreme Poultry and Grocery in East Oakland, which was one of the only Black-owned groceries in the Oakland area. Allen passed away on June 27, 1997.